Assessing cows’ mobility to determine their comfort state - Aliiev, E. B.; Алієв, Ельчин Бахтияр огли; Paliy, A. P.; Палій, А. П.; Korkh, O. V.; Корх, О. В.; Mykytiuk, V.; Mykytyuk, V. V.; Mykytiuk, V. V.; Mikityuk, V. V.; Mikitiuk, V. V.; Mykytiuk, Viktor; et al. (Oles Honchar Dnipropetrovsk National University, 2024)
Milk production and breeding of highly productive cows using modern innovative technologies have led to specific unfavorable combinations of technological factors in how cows are kept, which has significantly increased their susceptibility to developing various pathological processes in the musculoskeletal system. Lameness is the most common pathology. It is important to note that this information is based on objective evaluations and scientific research. The article is devoted to developing methodological approaches to determine the comfort state of cows based on mobility assessment. When determining the comfort state of a cow, in particular, the detection of diseases of the musculoskeletal system, a three-dimensional image of the animal was used, the position of the specified points of the animal's body was determined (tracking), the kinematic indicators of the movement of these points were calculated, the degree of bending of the animal's back during movement was assessed, complex mobility indicators were calculated, and the calculated complex mobility indicator was compared with the reference one. Based on the research results, a structural and technological scheme of a system for determining the comfort state of an animal based on the assessment of its mobility was developed, and software for video recording of movement was created. The step length, maximum step height, step duration, posture, and free state, as well as the speed of movement of healthy animals, those with single lesions and hoof ulcers were determined, and, as a result, the dynamics of changes in the accelerations of nodal points in the joints for each body link of healthy cows was revealed. The key variables of the biomechanical model for assessing the limbs of cattle (cows) are substantiated. The value of the specific force of the support reaction acting on the hooves of cows was determined: the highest value (9.8 N/kg) was observed for the concrete surface, the lowest (5 N/kg) – for rubber mats. The practical examples of the complex relationship between welfare indicators (lameness), elements of physiology (mobility), and technology (floor type) presented in the publication are recommended to be effectively used in monitoring the results of detecting gait disorders in animals and evaluating its effectiveness even in the early stages of the disease. The prospect of further research is to determine the comfort state of animals depending on environmental and climatic conditions. Виробництво молока та вирощування високопродуктивних корів за сучасними інноваційними технологіями призвели до специфічних несприятливих поєднань технологічних факторів утримання корів, що значно підвищило їхню схильність до розвитку різних патологічних процесів в опорно-руховому апараті. Кульгавість - найпоширеніша патологія. Важливо зазначити, що ця інформація базується на об'єктивних оцінках і наукових дослідженнях. Стаття присвячена розробці методичних підходів до визначення комфортного стану корів на основі оцінки рухливості. При визначенні комфортного стану корови, зокрема виявлення захворювань опорно-рухового апарату, використовували тривимірне зображення тварини, визначали положення зазначених точок тіла тварини (трекінг), кінематику. розраховували показники руху цих точок, оцінювали ступінь вигину спини тварини під час руху, розраховували показники комплексної рухливості та порівнювали розрахований показник комплексної рухливості з еталонним. За результатами досліджень розроблено структурно-технологічну схему системи визначення комфортного стану тварини на основі оцінки її рухливості та створено програмне забезпечення відеофіксації руху. Визначали довжину кроку, максимальну висоту кроку, тривалість кроку, позу і вільний стан, а також швидкість пересування здорових тварин, з поодинокими ураженнями та виразками на копитах і, як наслідок, динаміку змін у виявлено прискорення вузлових точок у суглобах для кожної ланки тіла здорових корів. Обґрунтовано ключові змінні біомеханічної моделі для оцінки кінцівок великої рогатої худоби (корів). Визначено значення питомої сили опорної реакції, що діє на копита корів: найбільше значення (9,8 Н/кг) спостерігалося для бетонної поверхні, найменше (5 Н/кг) – для гумових килимків. Наведені в публікації практичні приклади комплексного взаємозв’язку між показниками добробуту (кульгавість), елементами фізіології (рухливість) і технікою (тип підлоги) рекомендовано ефективно використовувати при моніторингу результатів виявлення порушень ходи у тварин та оцінці її ефективність навіть на ранніх стадіях захворювання. Перспективою подальших досліджень є визначення комфортного стану тварин залежно від екологічно-кліматичних умов.
Оцінка рухливості корів для визначення їх комфортного стану
Микитюк Віктор Васильович https://orcid.org/0000-0002-1346-490X
Keywords: floor type; підлоговий тип; cows; корови; musculoskeletal system; кістково-м'язова система; lameness; кульгавість; hooves; копита; mobility; мобільність